HEMATO-BIOCHEMICAL PROFILING OF A BURROWING CRAB EXPOSED TO POLYSTYRENE MICROPLASTIC CONTAMINANT - Moruf, Rasheed Olatunji; Sanni, Zakiat A.; Lawal-Are, Aderonke Omolara (FUDMA Journal of Sciences, 2020)
The study evaluated the effect of polystyrene microplastic contaminant on hemato-biochemical parameters of Cardiosoma guanhumi from the mangrove area of Lagos Lagoon using standard methods. Total Haemocyte Count (THC) ranged between 3050.00±0.00 mL and 4200.00 ±0.05 mL with control crabs having the highest value of 4200.00±0.05 mL. There was significant difference between the treatment groups and the control (p<0.05). Hemocyte sub-population variables showed that crabs fed the control and 0.01g polystyrene microplastic diets had higher granulocyte and monocyte populations but a decrease in agranulocytes. The crabs fed with the polystyrene microplastic contaminated diets were significantly higher in serum protein (32.50±0.05-32.90±0.10 gL-1) than the crab fed with control diet (20.09±0.05 gL-1). Crabs fed 0.01g and 0.02g polystyrene microplastic based diets recorded the same aspartate aminotransferase mean value (19.30 µI-1) which was significantly higher than the mean value (11.50 µI-1) recorded in crabs fed control diet. Crab fed 0.01g polystyrene microplastic based diet recorded most of the highest values for biochemical parameters: Alanine aminotransferase (13.00±0.05 µI-1), alkaline phosphatase (113.70±0.10 µI-1), lactate dehydrogenase (148.60±0.05 µI-1) and urea (40.41 ±0.15 µI-1). The changes in the crabs’ hematological and serum biochemical profiles in this study provide reliable and discriminatory data on the effect of microplastic contaminant calling for long-term monitoring to assess the eco-health of the mangrove system.